Feminist Ecologies Changing Environments in the Anthropocene (Springer International Publishing, 2018)
This edited collection critically engages with ecofeminist scholarship to better understand the contemporary and future challenges for feminism and environmental issues. It brings together key thinkers and activists in the field to map an ongoing dialogue between women's issues and rapid environmental change. Feminist Ecologies examines how ecofeminist thought and activism intersect with global debates about environmental catastrophe as a product of patriarchal capitalism and the status of women. Its chapters include contributions from pioneering scholars and activists in the field that engage with the tensions and concerns existing between historical feminism and ecofeminism. These include the dialectical relationship between environmental and feminist causes; the relational identities of feminists and ecofeminists; and the concept of ecofeminism as a new wave of feminism. This book helps to define ecofeminism as a multidisciplinary project and will be of particular interest to students and scholars of Gender Studies, Environmental Studies and Ecological Studies.